The impact of attention deficit hyperactivity disorder (ADHD) in adulthood: a qualitative study. (15th June 2017) - Watters, C.; Adamis, D.; McNicholas, F.; Gavin, B.
Abstract : Objectives: There is limited evidence of the unmet needs and experiences of adults with attention deficit hyperactivity disorder (ADHD). Previous research in this area is predominantly quantitative by nature, few studies employing qualitative approaches. This study seeks to provide a deeper insight into the lived experiences of adults with ADHD within Western Ireland. Methods: A qualitative design, consisting of semi-structured face-to-face interviews with a clinical sample in the Sligo/Leitrim area. Participants were eligible for this study if they screened positive for symptoms of ADHD, and diagnosed with ADHD with the Conners' Adult ADHD Diagnostic Interview for DSM-IV. In total, 11 participants completed this research. The interviews were open ended and exploratory, adopting a phenomenological approach. Results: Thematic analysis was used to explore three main themes; The Burden of symptoms of ADHD, Perceived Positive and Negative Effects of ADHD and Challenge of Accessing Services, each with several subthemes. Conclusion: This research highlights the experiences of adults with ADHD. It is important for practitioners to be aware of the perceived positive and negative effects of the disorder, and how it can impact on their patient's lives. In addition, becoming aware of the stigma associated with ADHD can help clinicians improve upon individual treatment plans to meet their patient's needs. It is important to note that this sample experienced co-morbid diagnoses and so this may limit the interpretation of the findings. Further research in this area could explore patient's attitudes towards receiving a formal diagnosis of ADHD.